Identification and validation of three diagnostic autophagy-related genes associated with advanced plaques and immune cell infiltration in carotid atherosclerosis based on integrated bioinformatics analyses - Tiegen Huang; Chen Su; Quanli Su; Yali Nie; Zhenni Xiao; Yao Tang; Jiahao Wang; Xiaotian Luo; Yixin Tang (PeerJ)
Background Autophagy plays a key role in the development of carotid atherosclerosis (CAS). This study aimed to identify key autophagy-related genes (ATGs) related with CAS using bioinformatics analysis, in vivo AS mouse model, and in vitro experiments. Methods The GSE100927 and GSE28829 datasets were downloaded from the Gene Expression Omnibus (GEO) database. An integrated bioinformatics analyses of differentially expressed ATGs (DE-ATGs) was conducted. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to identify the biological processes and pathways associated with DE-ATGs. Protein-protein interaction (PPI) network was constructed with the DE-ATGs to identify the key CAS-related DE-ATGs. Receiver operating characteristic (ROC) curve analysis was used to determine the diagnostic value of the key CAS-related DE-ATGs. CIBERSORT analysis was performed to determine the infiltration status of 22 immune cell types and their correlation with the expression levels of the key CAS-related DE-ATGs. Hematoxylin and eosin (HE) staining was used to estimate the plaque histology in the AS mouse model. Western blotting, quantitative real-time PCR (qRT-PCR), and immunohistochemistry (IHC) were performed to validate the protein and mRNA expression levels of the key CAS-related DE-ATGs in the in vitro and in vivo models. Results We compared transcriptome profiles of 12 early CAS plaques and 29 advanced CAS plaques in the GSE100927 dataset and identified 41 DE-ATGs (33 up-regulated and eight down-regulated). Functional enrichment analysis showed that the DE-ATGs were closely related with apoptosis, autophagy, and immune activation. ROC curve analysis showed that the area under the curve (AUC) values for the three key CAS-related DE-ATGs (CCL2, LAMP2, and CTSB) were 0.707, 0.977, and 0.951, respectively. CIBERSORT analyses showed close association between the three key CAS-related DE-ATGs and the infiltration of immune cell types in the plaques. Finally, the western blot, qRT-PCR, and IHC staining confirmed that CCL2, LAMP2, and CTSB were highly expressed in the plaques of the AS model mice or ox-LDL-treated human umbilical vein endothelial cells (HUVECs) and human aorta vascular smooth muscle cells (HAoSMCs). Conclusion We identified and validated three key CAS-associated ATGs, namely, CCL2, LAMP2, and CTSB with high diagnostic value. These three key CAS-associated ATGs are promising diagnostic markers and therapeutic targets for patients with CAS.